2016
DOI: 10.1108/tlo-01-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Learning in organization

Abstract: Purpose – This study aims at identifying the presence of the dimensions of learning capabilities and the characteristics of a learning organization within two companies in the field of services, as well as identifying the relationships between their learning capability and the organizational culture. Design/methodology/approach – This has been a transversal study on a convenience sample of 64 employees from two companies. The questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
11
0
2
Order By: Relevance
“…The LO has special significance in schools because an educational context becomes a place for training and innovation, where learning processes are performed that result in significant changes for the organization. In addition, a LO is seen as an effective organization in creating, acquiring and transforming knowledge (Davis and Lopuch, 2016), especially through the development of a culture that promotes confidence and shared values (Chu, 2016;Palos and Stancovici, 2016). In the words of Berkowitz et al (2013: 138), 'schools functioning as learning organizations have the capacity to use knowledge to successfully plan, implement, and evaluate strategies to achieve performance goals for individual students and the school as a whole'.…”
Section: Introductionmentioning
confidence: 99%
“…The LO has special significance in schools because an educational context becomes a place for training and innovation, where learning processes are performed that result in significant changes for the organization. In addition, a LO is seen as an effective organization in creating, acquiring and transforming knowledge (Davis and Lopuch, 2016), especially through the development of a culture that promotes confidence and shared values (Chu, 2016;Palos and Stancovici, 2016). In the words of Berkowitz et al (2013: 138), 'schools functioning as learning organizations have the capacity to use knowledge to successfully plan, implement, and evaluate strategies to achieve performance goals for individual students and the school as a whole'.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is required to examine the effects of other types of culture on organizational learning. Meanwhile and as only a few studies have empirically examined the association between organizational culture and organizational learning, the observations provide support and evidence of practical value for continuing relevant developments in this direction (Lindquist and Marcy, 2016;Palos and Stancovici, 2016). The addressed gap in the knowledge base can be further addressed through more targeted research.…”
Section: Discussionmentioning
confidence: 78%
“…Recent studies suggest that learning organizations could be found across different cultures (Kim and Marsick, 2013;Voolaid and Ehrlich, 2017). These organizations span across many industries such as manufacturing and services (Deli c et al, 2017;Palos and Stancovici, 2016) and health (Akhnif et al, 2017;Kumar et al, 2016). Systems thinking is often used to better understand how stakeholders are constantly responding to changes and interacting with each other in a dynamic health system (Rusoja et al, 2018).…”
Section: Case Illustrationmentioning
confidence: 99%